PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP TINGKAT PROFITABILITAS PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tri Kurniawati; Meria Fitri (Jurnal Praktik Bisnis, 2015)
This study aimed to analyze the impact of partially or simultaneously accounts receivable turnover and inventory turnover on the profitability of the  automotive and components company are listed on the Indonesian Stock Exchange. This research uses a quantitative approach.  The population used in this study is the automotive and components companies listed on the Indonesian Stock Exchange during the years 2007-2011 which amounts to 12 companies. Because of the relatively small number of companies, sampling is done with a total sampling method. The data was analyzed used regression analysis with panel data model. The research result shows that an increase in accounts receivable turnover does not significantly impact on the company's profitability of automotive and components company  listed on the Indonesian Stock Exchange during 2007 until 2011. Increased in inventory turnover also does not significantly impact on the company's profitability of automotive and components company listed on the Indonesian Stock Exchange during 2007 until 2011. For further research can continue for the analysis of other factors that affect the profitability of the automotive companies. Because in this study proved accounts receivable turnover and inventory turnover has no significant effect on the profitability of the the automotive and components companies listed on the Indonesian Stock Exchange Keywords: Account Receivable Turnover, Inventory Turnover, Profitability